2016
DOI: 10.1089/zeb.2016.1265
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Assessment in Zebrafish Embryos Exposed to Monceren® 250 SC Fungicide Using the Alkaline Comet Assay

Abstract: Monceren 250 SC is a commercial fungicide with the active ingredient 1-(4-chlorobenzyl)-1-(cyclopentyl)-3-phenylurea, also known as pencycuron. This compound inhibits the growth of fungi as Rhizoctonia solani that invades potato, rice, and cotton or as Pellicularia spp, which contaminates lettuce and tomato crops. In this study, we assessed genotoxicity or DNA damage by the alkaline comet assay in zebrafish blastula-stage embryos exposed to 250 to 1250 μg/mL of the Monceren fungicide or to Bleomycin (0.25 μg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In zebrafish, spirotetramat induced the downregulation of the fshr gene and the upregulation of the lhr gene, oxidative stress, and lipid peroxidation and delayed oogenesis and oocyte maturation and decreased the size of the ovaries (Wu et al, 2018). When comparing the genotoxic effects of the two keto-enol insecticides in ovaries from D. melanogaster, we observed that at low concentrations (11.2 mg/L), Movento® 240SC only increased tail intensity, which confirmed that this genotoxic parameter is very important to detect DNA damage in response to low concentrations of pesticide exposure (Ku-Centurión et al, 2016). Both high concentrations of Movento® 240SC (22.4 and 37.3 mg/L) produced more DNA damage.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In zebrafish, spirotetramat induced the downregulation of the fshr gene and the upregulation of the lhr gene, oxidative stress, and lipid peroxidation and delayed oogenesis and oocyte maturation and decreased the size of the ovaries (Wu et al, 2018). When comparing the genotoxic effects of the two keto-enol insecticides in ovaries from D. melanogaster, we observed that at low concentrations (11.2 mg/L), Movento® 240SC only increased tail intensity, which confirmed that this genotoxic parameter is very important to detect DNA damage in response to low concentrations of pesticide exposure (Ku-Centurión et al, 2016). Both high concentrations of Movento® 240SC (22.4 and 37.3 mg/L) produced more DNA damage.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, the term Drosophotoxicology has emerged due to the implementation of D. melanogaster in toxicology research in different stages (embryo, larvae, pupae, and adults) (Affleck and Walker, 2019) using different genetic assays, such as the comet alkaline assay to evaluate DNA damage by environmental pollutants, such metals (Mojica-Vázquez et al, 2019), nanoparticles (Alaraby et al, 2019) and pesticides (Misra et al, 2014). The alka-line comet assay is a genetic technique that is rapid and sensitive for detecting in vitro and in vivo genome strand breaks induced by agrochemicals (Ku-Centurión et al, 2016). The ovaries of D. melanogaster have been used to elucidate the genetic and molecular mechanisms of xenobiotics in the cell cycle, death, signaling, migration, differentiation, oogenesis, and development of the female reproductive system (Velentzas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline comet assay is a single cell gel electrophoresis technique widely used for sensitive detection of single and double strand DNA breaks in cells and tissue homogenates to measure the extent of genotoxicity of different materials. Several in vitro and in vivo studies with semiconductor quantum dots have shown increased genotoxic potential of these particles compared to their bulk counterparts . Carbon nanotubes and graphite nanofibers have shown dose-dependent and time-dependent increase in DNA damage in human bronchial epithelial BEAS 2B cells .…”
Section: Resultsmentioning
confidence: 99%
“…Recently Hylland et al [81] showed that the samples already embedded in agarose on gelbond films can be stored in lysis for several weeks which is a benefit in field studies. Additionally, the comet assay was modified also for whole fish embryos, usually zebrafish (Danio rerio) [88][89][90]. Recent studies have demonstrated that the embryos are a suitable biological model for environmental monitoring, as they are sensitive towards genotoxins in river water [90] and marine sediments [89], as well as chemicals such as fungicides [88] and polycyclic aromatic hydrocarbons (PAHs) [89].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Apart from using zebrafish as an in vivo model system, in addition to the zebrafish embryo model that can be regarded as an in vitro method, the use of zebrafish cultured cell lines in genetic toxicology is also on the rise [91,[97][98][99][100][101]. Up to now there have been more than 100 papers describing the zebrafish model both in vivo and in vitro using the comet assay for the assessment of different physical and/or chemical agents such as gamma rays [102,103], X-rays [104], pesticides [105], insecticides [106], fungicides [88,107], herbicides [108], mycotoxins [109], pharmaceuticals [98,99,[110][111][112], heavy metals A c c e p t e d M a n u s c r i p t 9 [108,113,114], PAHs [89], nanoparticles [115][116][117][118], flame retardants [119], sewage effluent [120], waste material [121] as well as model toxicants such as benzo(a)pyrene (B[a]P), methyl methanesulfonate (MMS) and ethyl methanesulfonate (EMS) [122,123].…”
Section: Accepted Manuscriptmentioning
confidence: 99%